Enlarging the victim's perspective on dehumanization. (April 2023) - Stinglhamber, Florence; Demoulin, Stéphanie
Abstract : Much of the research work on victims of dehumanization has focused on the conditions under which meta- and/or self-dehumanization occur among those who are the direct targets of dehumanizing treatments. We propose to enlarge this victim's perspective by considering it more holistically, extending it to perpetrators and observers of dehumanizing treatments. First, we suggest that when a dehumanizing treatment induces ethical dissonance in perpetrators, it is likely to generate subsequent meta- or self-dehumanization among them. Second, we argue that a dehumanizing treatment is likely to foster subsequent meta- or self-dehumanization among observers when it elicits negative emotions such as fear and guilt. Highlights: All individuals/groups that participate to dehumanizing treatments may be victims. Meta-/self-dehumanization occur among targets of dehumanizing treatments. Meta-/self-dehumanization may occur among perpetrators of dehumanizing treatments. Meta-/self-dehumanization may occur among observers of dehumanizing treatments